Administrative Support in Teaching and Learning of Physical Education in Colleges of Education in the Western Region of Ghana (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to investigate administrative support in teaching and learning of Physical Education in the Colleges of Education in the Western Region using descriptive survey design. Data was collected from a sample population of 90 respondents of first year students from Holy Child, Wiawso and Enchi Colleges of Education. Purposive sampling was used to select principals and P.E. tutors and convenient sampling was used to select the students. Descriptive statistic was used to analyse the data. The instrument developed for the study was questionnaire. It was revealed that most colleges do not have adequate facilities such as showers. Playing Courts like volleyball and netball were not available in their colleges. It is recommended that more supportive systems such as equipment, materials and facilities be provided to promote holistic and healthy college life for all trainees.